Financial Performance of Islamic Banks in Indonesia: Islamic Performance Indeks Approach - Marzukoh, Aliyatun; Rahmanto, Dhidhin Noer Ady; Irsyad, Syaiful Muhamad (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2023)
The purpose of this study was to determine the effect of the Islamicity Performance Index and Intellectual Capital on the profitability of Islamic Commercial Banks in Indonesia. The sample of this study was 7 Sharia Commercial Banks registered at Bank Indonesia and included in the Commercial Bank Business Activities (BUKU) II in 2018. This study used a multiple linear regression analysis method using Microsoft Excel 2007 and SPSS 20 software. Based on the result of testing, partial result of hypothesis showed that the variable Intellectual Capital (IC) has a positive signifivant effect on profitability of Comercial Sharia Bank in Indonesia, variable Equitable Distribution Ratio (EDR), Directors Employes Welfare Ratio (DEWR) has a positive not significant effect on profitability). Meanwhile the variable Profit Sharing Ratio (PSR) and Zakat Performance Ratio (ZPR) has a negative significant effect on profitability, and Islamic Income Ratio (IsIR) has a negative not significant effect on profitability of Comercial Sharia Bank in Indonesia. Simultaneous result of hypothesis showed that the all variable independent have positive effect on profitability, and variable dominan was Intellectual capital (IC).